Evaluation of the role of mitochondria in the non-targeted effects of ionizing radiation using cybrid cellular models - Miranda, S (2020)
Radiobiology is moving towards a better understanding of the intercellular signaling that occurs upon radiation and how its effects relate to the dose applied. The mitochondrial role in orchestrating this biological response needs to be further explored. Cybrids (cytoplasmic hybrids) are useful cell models for studying the involvement of mitochondria in cellular processes. In the present study we used cybrid cell lines to investigate the role of mitochondria in the response to radiation exposure. Cybrid cell lines, derived from the osteosarcoma human cell line 143B, harboring, either wild-type mitochondrial DNA (Cy143Bwt), cells with mitochondria with mutated DNA that causes mitochondrial dysfunction (Cy143Bmut), as well as cells without mitochondrial DNA (mtDNA) (143B-Rho0), were irradiated with 0.2 Gy and 2.0 Gy. Evaluation of the non-targeted (or bystander) effects in non-irradiated cells were assessed by using conditioned media from the irradiated cells. DNA double stranded breaks were assessed with the ¿H2AX assay. Both directly irradiated cells and cells treated with the conditioned media, showed increased DNA damage. The effect of the irradiated cells media was different according to the cell line it derived from: from Cy143Bwt cells irradiated with 0.2 Gy (low dose) and from Cy143Bmut irradiated with 2.0 Gy (high dose) induced highest DNA damage. Notably, media obtained from cells without mtDNA, the143B-Rho0 cell line, produced no effect in DNA damage. These results point to a possible role of mitochondria in the radiation-induced non-targeted effects. Furthermore, it indicates that cybrid models are valuable tools for radiobiological studies.